PERLINDUNGAN HAK PENDIDIKAN ANAK DI INDONESIA DALAM PERSPEKTIF ISLAM - Qurrotul Ainiyah; Fina Nihayatul Khusnah (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2019)
Education is one of the basic human rights possessed by every human being. This is due to the importance of education for humans, especially religious education. The religion of Islam gives first and foremost responsibility to parents who are given the mandate in terms of children's education. RI Law Number 20 of 2003 concerning the National Education System also regulates the noble goals of education in Indonesia which are rooted in religious values, the national culture of Indonesia and responsive to the demands of changing times. So that the right of children's education in the Act in the perspective of Islam is a manifestation of children's rights to get education in order to develop the potential of children as human beings and khalifah of God on earth.